Implementation of Merdeka Belajar Curriculum in the Process of Developing Independence and Creativity in Kindergartens in Juwana District: Implementasi Kurikulum Merdeka Belajar Dalam Proses Pengembangan Kemandirian dan Kreatifitas di Taman Kanak-Kanak Kecamatan Juwana - Handayani, Ita Kris; Diana; Hartono (Pendidikan Guru PAUD Universitas PGRI Semarang, 2025)
Abstract Based on preliminary observations at Juwana District Kindergarten, most of the learning process still focuses a lot on students' cognitive abilities so that students' independence and creativity are less developed. This study aims to determine the effect of implementing the Merdeka Curriculum on students' independence and creativity in kindergartens in Juwana District. This research is qualitative research. Research data were obtained through observations and interviews with principals, teachers, and parents of students. The results showed that the Merdeka curriculum has been implemented in Juwana District Kindergarten with a learning process tailored to the needs of students, creativity, and innovation in accordance with the objectives of the independent curriculum in accordance with applicable regulations. The implementation of the Merdeka Curriculum in Juwana District Kindergarten and the role of parents at home greatly help the development of early childhood independence so that the level of independence and creativity of students is mostly in the developing as expected category. These results indicate that the implementation of the independent curriculum has an effect on the development of students' independence and creativity in kindergartens in Juwana District. Keywords: Implementation, Kurikulum Merdeka, Autonomy, Creativity, Kindergarten Abstrak Berdasarkan observasi awal di Taman Kanak – Kanak Kecamatan Juwana, sebagian besar proses pembelajaran masih banyak berfokus pada kemampuan kognitif peserta didik sehingga kemandirian dan kreativitas peserta didik kurang dikembangkan. Penelitian ini bertujuan mengetahui pengaruh implementasi Kurikulum Merdeka terhadap kemandirian dan kreativitas peserta didik di Taman Kanak – Kanak Kecamatan Juwana. Penelitian ini merupakan penelitian kualitatif. Data penelitian diperoleh melalui observasi dan wawancara terhadap 4 orang kepala sekolah, 8 orang guru, dan 4 orang tua peserta didik. Hasil penelitian menunjukkan bahwa kurikulum Merdeka telah dilaksanakan di Taman Kanak-Kanak Kecamatan Juwana dengan adanya proses pembelajaran yang disesuaikan dengan kebutuhan peserta didik, kreativitas, dan inovasi sesuai dengan dapat tercapai tujuan dari kurikulum merdeka sesuai dengan peraturan yang berlaku. Implementasi Kurikulum Merdeka di Taman Kanak- Kanak Kecamatan Juwana dan peran orang tua di rumah sangat membantu perkembangan kemandirian anak usia dini sehingga diperoleh tingkat kemandirian dan kreativitas peserta didik paling banyak berada pada kategori berkembang sesuai harapan. Hasil tersebut menunjukkan bahwa implementasi kurikulum merdeka berpengaruh terhadap pengembangan kemandirian dan kreativitas peserta didik di Taman Kanak – Kanak Kecamatan Juwana. Kata kunci: Implementasi, Kurikulum Merdeka Belajar, Kemandirian, Kreativitas, Taman Kanak – Kanak